Small RNA Expression from the Human Macrosatellite DXZ4. Issue 10 (1st October 2014) - Pohlers, Michael; Calabrese, J Mauro; Magnuson, Terry
Abstract: Small noncoding RNAs play several roles in regulating gene expression. In the nucleus, small RNA-Argonaute complexes recruit epigenetic modifying activities to genomic sites. This pathway has been described in mammals primarily for the germline; however, its role in somatic cells is less characterized. Here, we describe in human somatic cells a potential link between the expression of small RNAs from the macrosatellite DXZ4 and Argonaute-dependent DNA methylation of this locus. DXZ4 was found to express a wide range of small RNAs potentially representing several classes of small RNAs. A subpopulation of these RNAs is bound by Argonaute. Moreover, we show AGO association with DXZ4 and that the Argonaute proteins AGO-1 and PIWIL4 may play a role in DNA methylation of DXZ4 . We hypothesize that the RNAs are involved in Argonaute-dependent methylation of DXZ4 DNA.